A comparison of the match action characteristics of scholarship, academy, and senior rugby league: influence on career progression - Bletsoe, J.; Whitehead, S.; Poolton, J.; Sawzcuk, T.; Till, K. (International Journal of Performance Analysis in Sport, 2024)
This study aimed to (1) compare individual player match action characteristics between scholarship, academy, and senior (European Super League, ESL) levels of the rugby league player pathway, and (2) compare match actions between players that have progressed to play ESL and those that did not. Data was collected on 147 players from 95 senior, 69 academy, and 23 scholarship matches over three seasons. Matches were filmed via 2 angles and 26 match action characteristics (e.g. carry, missed tackle) were coded. Linear mixed models identified 48 significant differences in match action characteristics when accounting for playing position between playing levels. Over seventy percent of the differences were defensive match actions, indicating there are higher defensive match demands in the ESL when compared to academy and scholarship match play. Seven and eleven match actions characteristics were identified at scholarship and academy levels that differentiated between players who had progressed to play in the ESL and those who had not. All but one of these characteristics were attacking match actions, indicating a player`s attacking qualities are important in their progression to the ESL. These results have implications for both talent identification and long-term athlete development in rugby league.